Unusual occurrence of dextrocardia with situs inversus in succeeding generations of a family. - Chib, P (1977)
In three cases of dextrocardia with situs inversus affecting a father and his two sons, the father had married his first cousin, the daughter of his father's sister, so that the two sons were the products of a consanguineous marriage. The general and familial incidence of the condition and the genetic influences responsible for it are discussed.